O amor em Lucrécio e Virgílio: um estudo comparado entre o início do Livro I e trechos do Livro IV do "De Rerum Natura" e as "Geórgicas" III - Darla Goncalves Monteiro da Silva (2016)
This work aims to demonstrate the treatment of amor in two works grouped by a typology of the didactic poetry, Lucretius' De Rerum Natura and Virgil's Georgics III. Specifically, the objects of study are the De Rerum Natura's Book IV (notably verses 1030-1287) and the Georgics' Book III (notably verses 209-283). The work also indicates relevant mentions of stretches of De Rerum Natura's and Georgics' other books, in order to expose a more embrancing vision, though brief, of the amor theme in the whole and only work of Lucretius and in the entire Virgil's book. Furthermore, this study presents a translation of De Rerum Natura's Book IV.